New Controllable Field Current Induced Excitation Synchronous Generator - Bei Wei; Xiuhe Wang (Institute of Advanced Engineering and Science, 2014)
The electrical machine using induced excitation system is a kind of brushless self-excited machine with low cost and high reliability, the induced excited machine would provide high power density at high-speed. But the low efficiency of the excitation system limits the development of this kind machine. Based on traditional excitation system, an improved construction induced excitation system is proposed in this paper. Adaptive control method is used to control the current direction in the stator auxiliary winding to replace constant DC excitation, the input current can change its direction according to the position of the rotor, the result is that all of induced currents at work in excitation system. Position sensors are fixed on the rotor and the stator field winding currents can synchronize with the rotor position according to the signal of the sensors. Experiments with the proposed structure are performed and compared with those of the traditional induced excitation system one. The results show that the new structure can improve the excitation system efficiency and reduce the cost.